High-Conversion-Ratio Bidirectional DC–DC Converter With Dual Coupled Inductors - Omid Khezri; Javad Javidan (Institute of Advanced Engineering and Science, 2014)
In this paper, a high-conversion-ratio bidirectional DC–DC converter with dual coupled inductors is proposed. In the boost mode, two capacitors are parallel charged and series discharged by the dual coupled inductors. Thus, high step-up voltage gain can be achieved with an appropriate duty ratio. In the buck mode, two capacitors are series charged and parallel discharged by the dual coupled inductors. The bidirectional converter can have high step-down voltage gain. The stress voltage of all switches can be reduced, and the switching loss and efficiency can be improved. The operating principle and the steady-state analyses of the voltage gain are discussed. Finally, in 24V for low voltage, and 400V for high voltage, and 200W for output power, this converter simulated in MATLAB.